Work Environment : How is It Influenced on Employee Performance? - Lusiana Tulhusnah; Puryantoro; Rasidi (International Journal of Science, Technology & Management, 2020)
The productivity of employee performance can be determined by the conditions of the work environment. This of course will affect the success of the agency in determining its goals. The research objective was to determine the effect of the work environment on the performance of the employees of Abdurachman Saleh University (Unars). Quantitative research methods with a population of 66 UNARS employees and saturated sampling technique so that the sample is also 66 respondents. The data used are primary and secondary data. The data were analyzed using t test, determinant test and simple regression model using SPSS 22. The results showed a simple regression model Y = -2.7596 + 0.622X. Work environment (X) has a significant effect on the performance of UNARS employees. The contribution of the work environment to employee performance is 38.7%, which means that there is a significant influence relationsh